PERAN MORFEM REFLEKTOR DALAM KONSTRUKSI VERBAL REFLEKTIF DALAM BAHASA DAWAN - Semuel Nitbani (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2020)
The Dawan language system shows a distinctive feature in terms of the clitization process of persona pronouns in the formation of verbs that carry out predicate functions in various sentence forms. The clitical forms of the persona pronoun play a variety of roles in forming the verb construction. One of them is a reflective verb. This reflective verbal construction is formed from reflective clitics or what is referred to in this paper as reflector clitics in their unity with the persona pronoun enclosure. Reflective verbal construction is a linguistic product that is still actively used in the community of owners and users of Dawan language. Consistency in using linguistic elements correctly shows the positive attitude of this society towards the language. Reflective verbal constructions are formed from the proclitic of the persona pronoun. the basic form, the reflector morpheme, and the enclosure of the persona pronoun. The basic principle of reflective verbal formation is the use of a reflector morpheme, namely -o-. Relatively speaking, this morpheme expresses the meaning of 'to oneself' which in use is unified with the persona pronoun enclit. The process of forming a reflective verbal construction can occur in the basic form of the persona pronoun's proximate word through the use of a reflector that is integrated with the enclitic of the persona pronoun. Both proclitic and enclitic in reflective verbal construction are the same persona pronoun.